Explanation of the Path of Dong Clothing Culture Dissemination under the Threshold of New Media - Wang, Lili (Journal of Ecohumanism, 2025)
Dong clothing culture has a rich cultural and historical background and a lengthy history. The emergence and acceptance of modern media has presented both new chances and difficulties for the spread of Dong clothing culture. In this research, we examine the cultural communication features of new media from the perspective of the importance of Dong clothing culture communication under the new media threshold and talk about the culture’s communication channel under the new media threshold. Through establishing awareness of new media communication, enhancing cultural self-awareness, and providing specific references for the communication and development of culture, it seeks to build a three-dimensional and diverse communication mechanism, build a communication platform for Dong clothing culture, and standardize and guide the communication order of national Dong clothing culture.